JURIDICAL REVIEW OF LAW NUMBER 6 OF 2023 CONCERNING EMPLOYMENT COPYRIGHT ON THE IMPLEMENTATION OF RISK-BASED BUSINESS LICENSING IN THE HEALTH SECTOR IN THE FIELD OF PHARMACY - PAHALA, ERIC SANDY; PANJAITAN, HULMAN; BETLEHN, ANDREW (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2024)
The fulfilment of medicines has become important in health development in Indonesia due to the increasing public awareness of health. Pharmacies are an important tool in the provision of medicines and health services. However, establishing a pharmacy business has high risks and requires a business licence and pharmacist practice permit. However, Law No. 11 of 2020 on Job Creation was rejected by the Constitutional Court, which resulted in the reissuance of the regulation in Law No. 6 of 2023. This has also impacted the regulations governing business licences, especially in the health sector such as pharmacies. Digital technology is also applied in implementing business licences with the OSS System. For the pharmacy business, business actors must understand the appropriate KBLI code and the correct licensing application procedure. Therefore, this research aims to analyse the impact of the reissuance of the rules in Law Number 6 of 2023 on the pharmacy business licensing rules. This research uses a form of normative juridical research that refers to developing legal norms, such as laws and court decisions. The approach methods used are statute approach and conceptual approach. The data to be used is secondary data from primary legal materials, secondary legal materials, and tertiary legal materials, such as laws, regulations, books, papers, journals, and other sources. The data collection technique that will be used is document study. The method of analysis that will be used is the qualitative analysis method to analyse the social aspects of the implications of Law Number 6 of 2023 on the Implementation of Risk-Based Business Licensing in the Health Sector for Pharmacies based on legal materials. After the issuance of Law Number 6 of 2023, there have been significant changes to the business licensing mechanism in Indonesia. Risk-based business licensing is enforced to support job creation and empowerment of micro, small and medium enterprises. The licensing process is based on the level of risk, with NIB as the legality to start and run a business. This concept regulates the function of NIB and other business licensing facilities from the government. Permenkes Number 14 of 2021 regulates the standards of business activities and products in the implementation of risk-based business licensing in the health sector, including pharmacies. So pharmacy business actors are encouraged to adjust to business licensing regulations and ensure legal certainty in pharmacy business licensing.